Non-rating revenue and conflicts of interest - Baghai, Ramin P.; Becker, Bo (Journal of Financial Economics, 2018)
Rating agencies produce ratings used by investors, but obtain most of their revenue from issuers, leading to a conflict of interest. We employ a unique data set on the use of non-rating services, and the associated payments, in India, to test if this conflict affects ratings quality. Agencies rate issuers that pay them for non-rating services higher (than agencies not hired for such services). Such issuers also have higher default rates. Both effects are increasing in the amount paid. These results suggest that issuers which hire agencies for non-rating services receive higher ratings despite having higher default risk.